A combined strategy to enhance phytosterols biotransformation to 22-hydroxy-23, 24-bisnorchol-4-ene-3-one by Mycobacterium neoaurum. (May 2023) - Cao, Dandan; Zhu, Xiaomei; Zhang, Jian; Wang, Xuedong
Abstract: A combined strategy for the overexpression of cholesterol oxidase M2 (ChoM2) and in situ removal of inhibitory intermediates was applied to promote the production efficiency of 22-hydroxy-23, 24-bisnorchol-4-ene-3-one (HBC) from phytosterols (PS) biotransformation by Mycobacterium neoaurum ( M . neoaurum ). Firstly, the rate-limiting step of PS to phytostenones was overcome by increasing the activity of ChoM2. Under this condition, PS transformation period was reduced from 84 h to 72 h, and the productivity of HBC was increased by 17%, in g/L/d from 9.36 (84 h) to 10.92 (72 h). Meanwhile, the overexpressed ChoM2 caused an excessive accumulation of the inhibitory intermediates, phytostenones, which hindered PS biotransformation. Accordingly, in situ removal of the inhibitory intermediates through adding 5 g/L of resin D101 (a macroporous styrene-divinylbenzene copolymer resin) at the beginning of the biotransformation further reduced the PS transformation time to 60 h, and the productivity was increased by 41% from 9.36 to 13.21 g/L/d. Graphical Abstract: ga1 Highlights: Overexpressing cholesterol oxidase in M. neoaurum promoted the sterols transformation. Inhibitory intermediate 4-ene-3-ketosteroids (phytostenones) were accumulated at 12 h. Addition of macroporous adsorbent resin D101 in situ removed the phytostenones.